ROMANTIKA KEHIDUPAN PADA LIRIK LAGU FOURTWNTY SEBAGAI PENGAYAAN BAHAN AJAR INTERAKTIF DALAM MATERI PUISI DI SMA - Aditya Fatur Rochim; Een Nurhasanah; Dian Hartati (Program Studi Pendidikan Bahasa Indonesia, STKIP Bina Bangsa Getsempena, 2021)
This research is motivated by the fact that students do not understand language styles. This study aims to (1) describe the results of the language style analysis on the album